KAP Study on Contraception of First Year Male Students in Khon Kaen University - Khotchawan Supa; Lingling Salang; Yuthapong Werawatakul; Kovit Khampitak; Keerati Wattanakamolchai (The Royal Thai College of Obstetricians and Gynaecologists, 2015)
Objective:To study knowledge, attitude, and practice of the first year male Khon Kaen university students regarding to contraceptionMaterials and Methods:A cross sectional descriptive study was conducted, using anonymous self-administered questionnaires, standardized by three staffs of reproductive gynaecology, in the first year male students who studied in first-semester undergraduate of academic year 2013.Results:670 male students were enrolled. Mean age was 18.6±0.96 years. One-fifth of male students (20.6%) had ever had sexual intercourse and most of them (45.7%) had sexual intercourse more than 4 times per month. Mean age at first sexual intercourse was 16.5±1.93 years.These groups had overall contraceptive used, excluded natural family planning, of 44.6 percent and 72.6 percent of them had contraceptive used of less than 80% of their sexual act. The most common contraceptive used was condom (32%). The main source of contraceptive information was from their friends (33.8%)Most of them (94.3%) had poor knowledge in contraception. Half of them (50.3%) accepted premarital sex. Most students had misperception about adverse effect of contraceptives. The poor knowledge score correlated with no contraception (P=0.027) and requirement of abortion if pregnancy occurred. (P=0.022) Conclusion:The majority of male students had poor knowledge in contraception, accepted premarital sex and misperception about adverse effect of contraceptives. Moreover, the majority of male students had the underuse, inappropriate use and misunderstandings in use of contraception despite having active sexual behaviors.